Use of IT–related Technologies in Hyderabad-based DRDO Laboratories: An Evaluative Study - Mohanta, G.C.; Thooyamani, K.P. (DESIDOC Journal of Library & Information Technology, 2010)
Improving productivity of knowledge workers is one of the major challenges in today’s global environment. Information technology-related technologies have given a new fillip to increase the productivity of those who are working in a knowledge-intensive organisation. This paper discusses the perspective of scientists of Hyderabad-based Defence Research and Development Organisation (DRDO) laboratories on usefulness of IT-related technologies on their performance. DOI: 10.14429/djlit.30.279